Pemilihan penyembuhan penyakit melalui pengobatan tradisional non medis atau medis - Ayu Setyoningsih; Myrtati D Artaria (Faculty of Social and Political Science, Universitas Airlangga, 2016)
This study regarding the selection of treatment between traditional medicine or medical treatment that is utilized by the community in an effort to cure disease. Doctors and shaman are two professions are known to the public, but using a different way. The aim of this research was to determine the meaning of a healthy and pain for the people of Jeru, know the reasons for choosing the traditional healing methods (shaman) or methods of medical treatment (doctor), and determine the factors that drive to determine the method of treatment. The method used in this study is a qualitative approach. The research location selected is Jeru Village, District Tumpang, Malang. This location was chosen as the study site because in this village still found a system of traditional medicine (shaman), and can still be found some medical personnel and some healers (shaman) are frequently visited by the public. Jeru’s people including homogeneous society. Determination of informants consists of 24 informants consisting of offender treatment, the patient, family, and also family health actors. In collecting the data, researchers used observation and interview techniques. Jeru’s society looked healthy and sick are people who feel the presence and absence of disturbances in the body when carrying out its activities. The reason for choosing a method of healing is based on trust, severity of illness, and the cause of the disease. The factors that drive a person to determine the treatment method chosen is based on internal and external factors. Internal comes from a person who wants a cure, while external factors derived from the experience of the people or the community who had suffered from the same disease, and healing which had healed. Early action before choosing between traditional healing or healing of the medical treatment itself. If it is the disease getting worse, then the sick person is looking for other relief efforts, which include traditional medicine, or medical treatment